Acute Short-Term Mental Stress Does Not Influence Salivary Flow Rate Dynamics - Naumova, Ella A. (Public Library of Science, 2012)
Background: Results of studies that address the influence of stress on salivary flow rate and composition are controversial. The aim of this study was to reveal the influence of stress vulnerability and different phases of stress reactivity on the unstimulated and stimulated salivary flow rate. We examined that acute mental stress does not change the salivary flow rate. In addition, we also examined the salivary cortisol and protein level in relation to acute mental stress stimuli. Methods: Saliva of male subjects was collected for five minutes before, immediately, 10, 30 and 120 min after toothbrushing. Before toothbrushing, the subjects were exposed to acute stress in the form of a 2 min public speech. Salivary flow rate and total protein was measured. The physiological stress marker cortisol was analyzed using enzyme-linked immunosorbent assay. To determine the subjects' psychological stress reaction, the State-Trait-Anxiety Inventory State questionnaire (STAI) data were obtained. The subjects were divided into stress subgroup (S1) (psychological reactivity), stress subgroup (S2) (psychological and physiological reactivity) and a control group. The area under the curve for salivarycortisol concentration and STAI-State scores were calculated. All data underwent statistical analysis using one-way analysis of variance. Results: Immediately after stress exposure, all participants exhibited a psychological stress reaction. Stress exposure did not change the salivary flow rate. Only 69% of the subjects continued to display a physiological stress reaction 20 minutes after the public talk. There was no significant change in the salivary flow rate during the psychological and the physiological stress reaction phases relative to the baseline. Conclusions: Acute stress has no impact on the salivary flow rate; however, there may be other responses through salivary proteins that are increased with the acute stress stimuli. Future studies are needed to examine specific proteins and their possible roles in acute stress responses.